Guided Imagery And Progressive Muscle Relaxation In Cancer Patients Undergoing Chemotherapy : A Literature Review - Agis Taufik; Nuriya (Journal of Bionursing, 2022)
ABSTRACT Introduction: Cancer is one of the health problems with a rapid increase in incidence and proven to be the second leading cause of death in the world today. Cancer is also a common problem that occurs in the elderly who suffer from the predicted increase in 605 million in 2000 to 2 trillion in 2050 (Shahriari et al., 2017). Therapy that is often done by patients is by doing chemotherapy, but by doing chemotherapy there are many side effects on the patient's physical and psychological. Interventions that can be given in addition to pharmacological drugs are alternative or complementary therapies. Independent intervention that can be done by nurses in patients given Progressive Muscle Relaxation (PMR) therapy and guided images (GI). Method: Search is done electronically using a database, including google scholer and sch from May 2019 to June 2019. The keywords used are "Therapy for Cancer Patients", "Guided Images & Progressive Muscle Relaxation in Cancer Patients" and "Progressive Muscles Relaxation" . Search uses the keywords above with the Google Scholer and Sci-Hub databases. Search results on Google Sholer and Sci-Hub obtained several articles. Results: Independent nursing interventions such as Progressive Muscle Relaxation (PMR) can be used in all stages of cancer and are known to reduce complications from cancer treatment (Shahriari et al., 2017). GI is a complementary therapy that can be applied under different conditions and at various participations to improve quality of life and decrease the risk of cancer (Shahriari et al., 2017). Discussion: GI and PMR interventions show strong evidence of the benefits of managing cluster considerations in prostate and breast cancer patients. In the intervention group compared with controls. Conclusion: PMR and GI interventions that address cancer patients who support Chemotherapy.